Images of “bread” / “non” and “salt” / “tuz” as cultural concepts in russian and uzbek linguocultures - Safarova, Laylo; Azizova, Nasiba Bakhritdinovna (The Lingua Spectrum, 2026)
The paper examines the material concepts “bread” / “non” and “salt” / “tuz” as key elements of material and spiritual culture in the Russian and Uzbek languages. The etymology and definitions of key lexemes, figurative perceptual features, symbolic meanings, as well as the phraseological and paremiological fund, ritual functions and representation of the concepts in folklore and fiction are analyzed. A comparative analysis reveals universal characteristics (bread as a symbol of life and prosperity, salt as a symbol of friendship and purity) and ethno specific features determined by differences in economic structure and religious traditions (Orthodoxy and Islam). Special attention is paid to the pair unity “bread salt” / “non tuz”, which in Russian culture emphasises the etiquette norms of hospitality, while in Uzbek culture emphasises the sacred nature of the bonds established through a shared meal.